Microbial management as a driver of parental care and family aggregations in carrion feeding insects - Körner, Maximilian; Steiger, Sandra; Shukla, Shantanu P. (Frontiers in Ecology and Evolution, 2023)
Social behaviors and lifestyles have evolved as successful strategies to cope with adverse and challenging living conditions, often by manipulating the immediate environment. These manipulations can extend to the surrounding microbiome, both in terms of combating harmful agents such as pathogens but also by facilitating the growth of beneficial microbes. In contrast to the largely antagonistic role traditionally assigned to microbes in social systems, these hostmicrobe interactions are receiving increasing attention as potential facilitators of social evolution. Here, we explore this perspective using Nicrophorus burying beetles, a group of insect carrion breeders which offer insights into the evolutionary interactions between sociality and microbial mutualists in a relatively simple family model. Recent studies have demonstrated the constant microbial challenges faced by Nicrophorus nurseries and the costly consequences they entail. Here, we provide an overview of these challenges and then explore the role of microbial mutualists in this social endeavor, focusing on the advantages they confer in terms of development and immunity. Additionally, we discuss how these mutualistic associations may select for committed parental care and more obligate forms of social life by promoting prolonged social associations through vertical transmission. Our review highlights the hypothesis that microbial mutualists not only provide immediate benefits but may also encourage social interactions in their hosts. However, the occurrence, degree, and underlying mechanisms of this phenomenon remain largely theoretical, as do the evolutionary feedbacks on microbes. Empirical evidence in this area is currently limited, emphasizing the need for further research. Nicrophorus burying beetles represent an ideal system to investigate the interplay between microbial mutualists and social evolution, offering a promising avenue for future studies. Overall, this review underscores the importance of understanding the complex interactions between microbial mutualists and social behaviors in challenging environments, and beyond.